N-benzyl-N-methyldecan-1-amine and its derivative mitigate 2,4- dinitrobenzenesulfonic acid-induced colitis and collagen-induced rheumatoid arthritis - Kim, Ji Eun; Kang, Changyu; Budluang, Phatcharaporn; Yawut, Natpaphan; Cho, Il-Rae; Choi, Yun Ju; Kim, Jaejeong; Ju, Sanghyun; Lee, Beomgu; Sohn, Dong Hyun; Yim, Hyung-Soon; Lee, Kyeong Won; et al. (Frontiers in Pharmacology, 2023)
As our previous study revealed that N-benzyl-N-methyldecan-1-amine (BMDA), a new molecule originated from Allium sativum, exhibits anti-neoplastic activities, we herein explored other functions of the compound and its derivative [decyl-(4-methoxy-benzyl)-methyl-amine; DMMA] including anti-inflammatory and anti-oxidative activities. Pretreatment of THP-1 cells with BMDA or DMMA inhibited tumor necrosis factor (TNF)-alpha and interleukin (IL)-1 beta production, and blocked c-jun terminal kinase (JNK), p38 mitogen-activated protein kinase (MAPK), MAPKAP kinase (MK)2 and NF-kappaB inflammatory signaling during LPS stimulation. Rectal treatment with BMDA or DMMA reduced the severity of colitis in 2,4-dinitrobenzenesulfonic acid (DNBS)-treated rat. Consistently, administration of the compounds decreased myeloperoxidase (MPO) activity (representing neutrophil infiltration in colonic mucosa), production of inflammatory mediators such as cytokine-induced neutrophil chemoattractant (CINC)-3 and TNF-alpha, and activation of JNK and p38 MAPK in the colon tissues. In addition, oral administration of these compounds ameliorated collagen-induced rheumatoid arthritis (RA) in mice. The treatment diminished the levels of inflammatory cytokine transcripts, and protected connective tissues through the expression of anti-oxidation proteins such as nuclear factor erythroid-related factor (Nrf)2 and heme oxygenase (HO)1. Additionally, aspartate aminotransferase (AST) and alanine aminotransferase (ALT) levels did not differ between the BMDA- or DMMA-treated and control animals, indicating that the compounds do not possess liver toxicity. Taken together, these findings propose that BMDA and DMMA could be used as new drugs for curing inflammatory bowel disease (IBD) and RA.